ARK 2016: AWI airborne ultra-wideband radar data in Northwest Greenland over the Hiawatha Glacier (Hiawatha project) - Olaf Eisen; Joseph A MacGregor; Horst Machguth; Daniel Steinhage; Veit Helm; Tobias Binder (PANGAEA, 2025)
This dataset contains airborne radar data acquired using the AWIs multi-channel ultra-wideband radar system (AWI UWB) during the Arctic season of 2016. The profiles extend across the Northwest Greenland Ice Sheet over the Hiawatha Glacier covering the Hiawatha impact crater. The data are available as netCDF files (including waveforms and metadata), KML files of the profile line locations, and quicklook images of the radargrams.